WOLFF-PARKINSON-WHITE SYNDROME IN ATHLETES - Furnadjiski, Atanas; Georgiev, Antonio (Faculty of Physical Education, Sport and Health in Skopje, Republic of Macedonia, 2023)
A clinical syndrome named after the cardiologists Louis Wolff, Sir John Parkinson, and Paul Dudley White in 1930, when this heart rhythm disorder was first described, became an important condition in the athlete population because of its possible fatal and unexpected consequences. In the very essence of this pathological condition is an anatomic substrate called an aberrant pathway of Kent- an interposed connective tissue bond between the normal conductive system of the heart. This accessory pathway in circumstances of fast heart rhythm can and will become a fast gate for normal impulse conduction which will result in arrhythmia such as “reentrant” supraventricular tachycardia (AVRT) or atrial flutter (AF) which might degenerate in lethal ventricular fibrillation leading to a sudden cardiac death (SCD) in the athletes. This occurs when the normal impulse of the sinoatrial node travels down the AV node add Hiss Purkinje system and returns in a retrograde manner to the atrium via the accessory pathway. AVRT can be orthodromic, following the normal physiological route, or antidromic when the depolarization wave follows the opposite route of physiologic conduction.